Kepuasan Masyarakat pada Program Kampung Sehati (Corporate Social Responsibilty PT. PLN Indonesia Power Suralaya PGU) - Nugroho, Kandung Sapto; Sjafari, Agus; Syaefulloh, Syaefulloh (International Journal of Demos (IJD), 2023)
AbstrakThis article tries to understand public organizations not only in government institutions which are presented as bureaucracies such as public services in the field of education, health from local governments or hospitals or schools, but also in their appearance as corporations. PT. PLN Indonesia Power Suralaya PGU is a clear example of a public organization in the form of state representation in corporate form. The use of survey methods in preparing the community satisfaction index will produce a detailed level of community satisfaction that is measured. This database will be used as material for preparing policies/programs that can be improvised, monitored or evaluated so that relations with external organizations will be more constructive. The overall performance of the community satisfaction index for the Sehati Village Program reached 84,066, in the Very Good category. In order to maintain and improve community empowerment performance, this study recommends establishing a technical communication forum between empowerment actors with regular meetings and discussing potential technical problems that arise. Based on these findings, this study provides recommendations for internal PT. PLN Indonesia Power Suralaya PGU takes the form of establishing a technical communication forum involving multi-stakeholder community development.Keywords: Â Empowerment, Kampung Sehati, Indonesia Power.Â AbstrakArtikel ini mencoba memahami organisasi publik bukan hanya pada lembaga pemerintahan yang ditampilkan sebagai birokrasi seperti layanan publik bidang pendidikan, kesehatan dari pemerintah daerah atau rumah sakit atau sekolah, namun juga dalam tampilan sebagai korporasi. PT. PLN Indonesia Power Suralaya PGU merupakan contoh nyata organisasi publik dalam tampilan representasi negara dalam bentuk korporasi. Penggunaan metode survei dalam penyusunan indeks kepuasan masyarakat akan menghasilkan tingkat kepuasan masyarakat yang terukur secara detail. Basis data inilah yang akan dijadikan bahan penyusunan kebijakan/program yang sifatnya bisa improvisasi, monitoring maupun sebagai evaluasinya sehingga relasi dengan eksternal organisasi akan bisa lebih konstruktif. Kinerja secara keseluruhan indeks kepuasan masyarakat pada Program Kampung Sehati mencapai 84,066, berkategori Sangat Baik. Guna mempertahankan dan meningkatkan kinerja pemberdayaan masyarakat, maka kajian ini merekomendasikan pembentukan forum komunikasi teknis antar aktor pemberdayaan dengan pertemuan rutin dan membahas potensi masalah-masalah teknis yang muncul. Atas dasar temuan inilah kajian ini memberikan rekomendasi bagi internal PT. PLN Indonesia Power Suralaya PGU berupa pembentukan forum komunikasi teknis dengan melibatkan multi stakeholder community development.Kata kunci: Pemberdayaan, Kampung Sehati, Indonesia Power.